2014
DOI: 10.1149/2.025405jss
|View full text |Cite
|
Sign up to set email alerts
|

Surface Planarization of GaN-on-Sapphire Template by Chemical Mechanical Polishing for Subsequent GaN Homoepitaxy

Abstract: The possibility of chemical mechanical polishing (CMP) as an intermediate ex-situ surface planarization process for thin-film epitaxy devices has been investigated. The surface quality of the homoepitaxial GaN after a surface pretreatment of CMP on the GaN-on-sapphire template drastically improved as compared to that with the regular homoepitaxial process. In addition, it was found that CMP contributed to a reduction in the dislocation densities in the subsequent homoepitaxial GaN layers. The CMP-treated GaN s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…A removal rate with a colloidal silica slurry as low as 17nm/h has recently been reported [19]. Thus it is important to improve the CMP removal rate, which can realize acceleration of the next generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…A removal rate with a colloidal silica slurry as low as 17nm/h has recently been reported [19]. Thus it is important to improve the CMP removal rate, which can realize acceleration of the next generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, the full benefit of the nitride devices has not been realized due to the lack of commercially available, high quality native nitride substrates [7][8]. GaN samples have been grown with several different techniques, including high-temperature high-pressure near equilibrium growth [9][10], sodium flux method [11], ammonothermal method [12], metal organic chemical vapor deposition (MOCVD) [7,13] and hydride vapor phase epitaxy (HVPE) [14][15][16][17]. Only the HVPE technique has demonstrated the potential of producing large diameter GaN [18][19][20].At present, the principle substrates on which III nitride-based materials devices are commercially grown and fabricated are sapphire and silicon carbide (SiC) due to their stability in the high-temperature and hydrogen-containing growth environment as well as their availability.…”
Section: Introductionmentioning
confidence: 99%
“…The devoted efforts and experiences of previous researchers in the development of mechanical processing of sapphire can be applied to the mechanical process of GaN. Although Hideo Aida et al found that gallium face of GaN was able to polish with colloidal silica slurry [31], the remove rate of GaN in CMP with colloidal silica exhibits a range of 10 to 100 nm per hour due to strong chemical inertness [29,30,[32][33]. Assuming that the depth of the damaged layer to be removed by CMP and the removal rate are 1.6 mm and 40 nm/h, respectively, the processing time will be 40 h, which means this is not a practical method for commercial production.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Because the surface quality of GaN grown by heteroepitaxy is defective, chemical mechanical polishing plays a very important role in wafer processing. [5][6][7] In 2015, Hideo Aida et al expounded the importance of GaN surface oxidation in the CMP process, and they indicated that the oxidation rate on the wafer surface was the key factor limiting the removal rate of GaN materials. 8 In 2016, Jie Wang et al studied the effect of UV intensity on the removal rate of materials and concluded that the addition of UV light could improve the MRR.…”
mentioning
confidence: 99%